Hegel's Twilight : Liber Amicorum Discipulorumque Pro Heinz Kimmerle. - Ramose, Mogobe B. (Studien zur interkulturellen Philosophie / Studies in Intercultural Philosophy / Études de philosophie interculturelle, 2013)
Professor Heinz Kimmerle encountered African philosophy at a time when his specialisation in the philosophy of Hegel had attained world recognition. For Hegel, African philosophy did not exist in Sub-Saharan Africa, exactly the area in which Kimmerle made his first contact with African philosophy. Hegel's philosophy was not a stranger to Sub-Saharan Africa. This was because the Western educational paradigm was imposed upon the conquered, colonized peoples during the period of colonisation. Unlike Hegel, Kimmerle took African philosophy seriously and engaged, initially, in dialogues with African philosophy. Out of the unfolding dialogues grew intercultural philosophy spearheaded by Kimmerle's penetrating, insightful and incisive critique of some of the fundamental presuppositions of Hegel's philosophy. The essays contained in this book focus on the evolution of Kimmerle's conception and meaning of intercultural philosophy. Underlying this are recognition and respect for other modes of doing philosophy as manifestations of intercultural philosophy. To deny dialogues, if you prefer, polylogue among world philosophies, is to reject the very basis of philosophy. Thus a crucial dimension of philosophy would be precluded, which can be found in this book, namely, the critical evaluation of Kimmerle's conception and meaning of intercultural philosophy.